Teka Ra Ne’e: The Integration of Islamic Values and Local Culture in Strengthening Community-Based Economic Development and Customary Law in Bima - Amrin; Muhammad Dwi Fajri; Emil Salim; Amirullah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The Teka Ra Ne’e culture in Bima society reflects the strength of the gotong royong tradition that has long been an integral part of their social life. This study examines the values ​​contained in the Teka Ra Ne’e culture and how these values ​​contribute to developing a community-based economy in Bima. This tradition, which involves voluntary community participation in assisting in the form of food, labor, and other resources, not only functions as a local cultural practice, but also as an implementation of Islamic values ​​that support social solidarity, justice, and social responsibility in society. This study uses a qualitative method with a field study with an ethnographic approach that includes observation, interviews, and documentation. Data analysis techniques used include data reduction, data presentation, and conclusion. The results of the study show that Teka Ra Ne’e plays a role as a pillar in building an inclusive and sustainable community-based economy while creating harmony between religious and cultural values ​​in supporting socio-economic development in Bima. This study contributes to the understanding of how local traditions, rooted in spiritual and social principles, can transform to meet the challenges of the modern economy. By upholding the values ​​of solidarity, justice and social responsibility, Teka Ra Ne’e is a real example of community-based economic development that can be applied in the context of a developing society.